A new species of Neoatriplectides Holzenthal, 1997 (Insecta: Trichoptera: Atriplectididae), from Brazil, including description of the pupa of the genus - Dumas, Leandro Lourenço; Nessimian, Jorge Luiz (Zootaxa, 2008)
The adult male and pupa of a new species of the genus Neoatriplectides Holzenthal, 1997, are described and figured based on specimens collected in the Mantiqueira Mountain Range, southeastern Brazil. A male of Neoatriplectides desiderata, sp. nov., was associated with the unidentified larva described by Holzenthal, 1997. The new species is differentiated from N. froehlichi Holzenthal, 1997, mainly by the division of abdominal segment X into 2 triangular projections, absent in N. froehlichi. The pupal description is the first for this genus.